2019
DOI: 10.1002/asia.201900905
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Relaxation Processes of Conjugated Polymer Nanoparticles in the Presence of Au Nanoparticles

Abstract: Considering the importance of conjugated polymer nanoparticles, major emphasis has been given for designing and understandingt he energy transfer and charge transfer processes of organic-inorganic hybridsf or light harvesting applications.I nt he present study, we have designed an aqueous solution-based light harvesting system using conjugatedp olymer nanoparticles (poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylenevinylene],M EH-PPV) and Au nanoparticles. The change in photo-induced processes in the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Here, the GSB peak at 525 nm is slightly blue-shifted from the plasmon band position of the Au NP. Therefore, the bleach at 525 nm in SADS3 does not arise due to energy transfer from F8BT PNP to Au NP; rather, SADS 3 is a signature of a charge-transfer state arising due to thermodynamically driven electron transfer from S 1 state of the F8BT PNP to Au NP. , The significant reduction of S 1 state from 45 to 12.5 ps as compared to the pure F8BT PNP confirm the electron transfer process. Therefore, we ascribe SADS 3 for charge transfer state S 1 δ+ –Au NP δ‑ and the time scale associated with the electron transfer from the S 1 state of F8BT PNP to Au NP is 6.8 ps (Figure C) (detailed calculation of time scale is provided in the Supporting Information).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Here, the GSB peak at 525 nm is slightly blue-shifted from the plasmon band position of the Au NP. Therefore, the bleach at 525 nm in SADS3 does not arise due to energy transfer from F8BT PNP to Au NP; rather, SADS 3 is a signature of a charge-transfer state arising due to thermodynamically driven electron transfer from S 1 state of the F8BT PNP to Au NP. , The significant reduction of S 1 state from 45 to 12.5 ps as compared to the pure F8BT PNP confirm the electron transfer process. Therefore, we ascribe SADS 3 for charge transfer state S 1 δ+ –Au NP δ‑ and the time scale associated with the electron transfer from the S 1 state of F8BT PNP to Au NP is 6.8 ps (Figure C) (detailed calculation of time scale is provided in the Supporting Information).…”
Section: Resultsmentioning
confidence: 83%
“…This is because excitons are predominantly generated upon photoexcitation, and the PL decay represents the depopulation of charge carrier. Favorable interchain interactions between different chromophoric subunits with different energy levels along polymeric backbone leads to exciton diffusion (energy migration in form of exciton) from blue absorbing subunits to low lying red subunits after excitation. ,, It is evident that these energy funneling occurs in a collapsed state through a delocalized collective state which is the lowest energy sites of the collapsed form. ,,,,, Interestingly, the diffusion length is found in the range of ∼2 nm for all of the systems, and the size of the pristine polymer nanoparticle is around 40 nm. Thus, the generated excitons after photoexcitation migrate through the chromophoric subunits and those excitons residing at the periphery of the nanoparticles can transfer from the polymer nanoparticle to the Au nanostructure.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Reisner and co-workers have realized as many as 398 μmol of photocatalytic H 2 production per gram of C-dots per hour in the presence of a nickel co-catalyst . Significant efforts have been devoted to the synthesis and applications of C-dots; however, the study of the excited-state relaxation of C-dots using ultrafast spectroscopy and global and target analysis is less explored, which is essential for the development of efficient light-harvesting systems. Wang et al have proposed an intrinsic dark state and a surface-related emissive state, which relaxes independently in the case of a carbon nanodot . On the contrary, previous works report the excitation transfer from the core to surface with various time scales ranging from 400 fs to 10 ps. , Yang and co-workers have demonstrated a detailed interplay between the core and surface in the excited state. , Wen et al have identified the time scale for various processes for the excited state of C-dots such as surface trapping (400 fs), optical phonon scattering (<5 ps), acoustic phonon scattering (50 ps), and excitonic recombination (1.5 ns) .…”
mentioning
confidence: 99%
“…Understanding the essential structure–property correlation and the relaxation dynamics of multichromophoric organic aggregated materials is very important for designing potential materials for organic electronics, sensing devices, photocatalysis, and light-energy conversion devices. The temperature, solvent effect, concentration, and solubility are the decisive factors for molecular aggregation. Intermolecular interactions like π–π stacking, hydrogen bonding, hydrophobic or electrostatic interactions, van der Waals forces, etc., alter with the degree of molecules’ aggregation. All of those mentioned above eventually control the photophysical behavior. Therefore, a systematic study is required to understand the excited state dynamics with varying aggregation degrees, which will benefit artificial light-harvesting systems. …”
mentioning
confidence: 99%